DETERMINATION THE OPTIMUM CONDITIONS OF LACCASE PRODUCTION FROM LOCAL ISOLATE OF STREPTOMYCES SP. USING SOLID STATE FERMINTATION - & et al., Hussein (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
Six different bacterial and fungal isolates included Pseudomonas sp., Bacillus sp., Candida sp., Klaveromyces sp., Aspergillus sp. and Streptomyces sp. were tested to produce laccase enzyme by using submerged fermentation, Streptomyces sp., Candida sp., and Pseudomonas sp. were chosen as being the heaviest in terms of enzyme production, and were tested for laccase production by solid state fermentation using different supports such as a solid media including sawdust with 0.06% xylene, sawdust and bran mixture (2:1) with 0.06% xylene. By using a combination of sawdust and bran (2:1), the productivity of laccase produced from Streptomyces sp., Candida and Pseudomonas sp. reached 177.8, 144.3 and 103.46 U. g-1 respectively. Streptomyces sp., isolate was chosen for laccase production. Optimum conditions for laccase production was determined from the selected isolate Streptomyces sp. by using an amalgamation of sawdust and bran (2:1) in pH 5.5 and the medium was incubated at 30oC for 14 days. This specific activity for laccase enzyme reached 1315 U.mg-1. The maximum removal efficiency of textile dyes such as (yellow, red and black) by crude laccase was reached 87%, 43% and 74% respectively after a period of 3 hours.